Merdeka Belajar: Solusi Revolusi Pendidikan di Indonesia - Miftah Fadhillah; Masduki Asbari; Eiffeline Melati Octhaviani (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to respond to education problems in Indonesia which is experiencing a learning crisis. This study report uses a qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Youtube channel entitled